Nutrition Features of Medical University Students - Tashmamatov Sherzod Xolmamatovich; Nabiev Ulugbek Nemat ogli (Zien Journals, 2024)
The problem of health protection and prevention of diseases, the development of which is partially or completely related to nutrition, remains quite relevant. The student period is very rich and varied, characterized by great tension in all functional systems of the body. Analysis of the nutrition of students using a questionnaire method showed that the nutrition of the subjects was irrational due to a violation of quantitative and qualitative characteristics. The diet is monotonous, characterized by a lack of vegetables, fruits, dairy products, meat, and an excess of fast food products. Most of the respondents have dyspeptic disorders. At the same time, a third of respondents have pathology in the digestive system. The results obtained are useful for solving the problem of organizing students' meals.
Keywords: students; diet; rational nutrition